Modernity and functionality: relooking changes in Chinese vernacular education in Singapore, 1919-1941 - Ho, Amanda Shi Min (Nanyang Technological University, 2022)
The history of Chinese vernacular education in Singapore prior to the Japanese Occupation from 1942 to 1945 is often overlooked in the scholarship of Chinese education in Singapore. There are three stages of Chinese vernacular education prior to the Japanese Occupation and these stages are correlated to the type of schools that exist, firstly, traditional reading schools, secondly, new-style schools, and thirdly, modern Chinese schools. The differences between these stages are based on changes in the school’s curriculum and management, which are premised on the idea of “modernity”. This thesis focuses on the final stage – modern Chinese schools. I argue that modern Chinese schools in Singapore started around 1919 to the start of the Japanese Occupation in 1942 as it was the period when the schools had shed their “traditional” elements from traditional reading schools. These changes in Chinese vernacular education did not happen for no reason – the changes were a result of the interaction between the modern Chinese school and society, which can be seen from: (1) its role as an institution, (2) its knowledge forms, and (3) its educators and funders. The role of schools as an institution is observed through broader changes in Chinese vernacular education as a whole and I consider 1919 to 1942 to be the “Rise in Chinese Education” as it was a period when many Chinese schools as institutions became increasingly relevant to the Chinese community in Singapore. The knowledge forms can be observed from the curriculum changes in school and the educators and funders from the management of the schools. By looking at the changes in Chinese vernacular education over time, this thesis aims to answer a few questions: (1) How do we make sense of the historical trajectory of Chinese vernacular schools in pre-war Singapore? (2) How do we situate schools within its community? (3) What are the functions of schools and from where do we observe these functions? This thesis aims to reconstruct the history of modern Chinese schools in Singapore from 1919 to 1941, reexamining what has been covered thus far in both English and Chinese scholarship of the history of Chinese vernacular education in Singapore and synthesising the findings of both strands of scholarship. This thesis also aims to look beyond the study of political time markers to draw out the possible socio-cultural and economic factors that led to these changes.